DISCRETE CALCULUS ANALYSIS OF POVERTY DYNAMICS IN JAYAPURA REGENCY, 2017–2024, BASED ON SDG GOAL 1 - Marthinus Yohanes Ruamba; Ortis Fredy Waromi; Natan Baransano (International Journal of Multidisciplinary Reseach, 2026)
Poverty in Jayapura Regency, one of the buffer areas of Papua Province’s capital region, is a key challenge in achieving the Sustainable Development Goals (SDGs) Goal 1: No Poverty. This study aims to analyze the rate of change and dynamics of poverty in Jayapura Regency for the period 2017-2024 and project it to 2030 using a discrete calculus or finite-difference approach. The research method is quantitative descriptive with secondary data on the percentage of the poor population from the Central Statistics Agency (BPS). The analysis was conducted by calculating the first derivative (rate of change) and the second derivative (acceleration/deceleration) discretely. The results show that the poverty rate declined from from 13.01% (2017) to 11.60% (2024). However, derivative analysis reveals a significant deceleration phase in the 2022-2024 period, culminating in a a reversal to a positive rate of change (+0.15 percentage points) in 2024. This critical finding suggests that the post-pandemic momentum for poverty reduction has weakened and is beginning to reverse. Simple linear projections up to 2030 indicate that the SDG target for eliminating extreme poverty is at risk of being missed without significant policy acceleration. The differential calculus approach has proven effective as an early detection tool for detecting changes in momentum that are not always visible from static annual data.